Establishment of an FDA-approved international Better ProcessControl School for food canning supervisors - Avena-Bustillos, R. J. (Progress in Nutrition, 2011)
Summary Foreign manufacturers of acidified and low-acid canned foods who export to the United States must comply with provisions of Title 21, Code of Federal Regulations (CFR), Parts 108, 113, and 114. The regulations require that all operators of retorts, thermal processing systems, aseptic processing and packaging systems and container closure inspectors shall be under the operating supervision of a person who has attended a school approved by the Commissioner for giving instruction appropriate to the preservation technology involved and who has been identified by that school as having satisfactorily completed the prescribed course of instruction. The purpose of the Better Process Control School (BPCS) is to help food canneries to meet the safety requirements set by the United States CFR, which are to ensure safety from harmful bacteria and their toxins, especially Clostridium botulinum. The United States Food and Drug Administration (FDA) approve these schools, and those who successfully pass the course are registered with the FDA. A number of foreign entities have sought assistance from FDA to present a BPCS often as a means to upgrade their countries acidified and low-acid canned food industry or to become more informed about the United States’ regulatory requirements for these industries in order to facilitate importing into the United States of America. Because of the obvious benefits, the FDA has not discouraged these efforts. However, past experience has demonstrated the necessity for FDA’s Center for Food Safety and Applied Nutrition (CFSAN) to participate from the beginning in directing efforts to establish a “school”, reviewing specific plans for its conduct, as well as participating in and monitoring any “school”. Obviously, for a successful program of this type, maintenance and uniformity of “school” conduct, content and performance standards are important considerations in the FDA/CFSAN decision regarding approval. In this presentation we will discuss some basic components of the BPCS and procedures to work with the CFSAN to present a regular school that can be considered an official “BPCS” authorized by the FDA and which may be approved by the Commissioner of FDA and may be presented a number of times in the future by a foreign istitution. Istituzione di una Better Process Control School approvata dalla FDA a livello internazionale per i supervisori di alimenti conservati in scatola Riassunto I produttori esteri di alimenti conservati in scatola, acidificati e a bassa acidità, che esportano verso gli Stati Uniti devono conformarsi alle disposizioni del Titolo 21 del Codice di Regolazione Federale (CFR), parti 108, 113 e 114. Le normative prevedono che tutti gli utilizzatori di storte, di sistemi di trattamento termico e di sistemi di lavorazione e di confezionamento asettico e gli ispettori di chiusura dei contenitori devono essere sottoposti alla supervisione operativa di una persona che ha frequentato e completato con successo l’istruzione prescritta dalla scuola approvata dall’FDA. Lo scopo della Better Process Control School (BPCS) è quello di aiutare le industrie conserviere alimentari a soddisfare i requisiti di sicurezza fissati dal CFR degli Stati Uniti, che devono garantire la sicurezza da batteri nocivi e dalle loro tossine, in particolar modo il Clostridium botulinum. L’Agenzia per gli alimenti e i medicinali americana (FDA) approva queste scuole, e coloro che superano il corso sono registrati presso la FDA. Un certo numero di soggetti stranieri ha cercato assistenza da parte della FDA per presentare una BPCS spesso come mezzo per aggiornare i propri paesi sulle procedure relativamente ai cibi acidificati e a bassa acidità dell’industria conserviera alimentare o per essere più informati sui requisiti in materia regolatoria degli Stati Uniti per facilitare l’importazione in questo paese. A causa dei benefici evidenti, la FDA non ha scoraggiato questi sforzi. Tuttavia, l’esperienza passata ha dimostrato la necessità per la FDA di un Centro per la Sicurezza Alimentare e la Nutrizione Applicata (CFSAN) per partecipare fin dall’inizio nel dirigere gli sforzi per creare una “scuola”, rivedendo i piani specifici per la sua condotta, così come nel partecipare e monitorare qualsiasi “scuola”. Ovviamente, per il successo di un programma di questo tipo, il mantenimento e l’uniformità della condotta della “scuola”, lo standard di contenuti e di prestazioni sono considerazioni importanti nell’approvazione di decisioni riguardanti la FDA/CFSAN. In questo lavoro si discuterà di alcune componenti fondamentali della BPCS e delle procedure per lavorare con il CFSAN per presentare una scuola regolare, che possa essere considerata una “BPCS” ufficiale autorizzata dalla FDA, approvata dal Commissario della FDA.